Community leaders' characteristics and their effort in building community capacity for tourism development in local communities - Aref, Fariborz; Redzuan, Ma'rof (Canadian Center of Science and Education, 2009)
Community leaders are an important element of any community and vital to successful community development. In a community capacity approach, community leaders play a vital role in handling the programs and plans towards achieving the goals of the community.This paper investigates relationship between the community leaders’ characteristic and their effort in building capacity for tourism development in local communities of Shiraz, Iran. The results from Pearson correlation showed that there was a significant positive correlation between age, length of residence, length of position held, income with level of community capacity building in tourism development. Spearman rho correlation also found there was a significant positive correlation between educational level, tourism income, extra activities, tourism jobs, and family engaged in tourism activities with level of community capacity building in tourism development.